Beim Übergang zum Bürgergeld mutig große Veränderungen wagen; Introducing the citizen's income (Bürgergeld): Making bold changes - Alexander Herzog-Stein (Wirtschaftsdienst, 2022)
– The new German federal government wants to replace the unemployment benefit II (Arbeitslosengeld II) with a so-called citizen's income ("Bürgergeld"). In doing so, it needs to make major changes. Measures outlined in the coalition agreement indicate that the existing imbalance in the so called support and claim-approach ("Fördern und Fordern") for the long-term unemployed will be finally readjusted towards supportive policy measures such as training. The reform of the in-work benefit element should aim at supporting sustainable employment subject to social security contributions. However, to live up to its name, the citizen's income must ensure genuine social participation for those receiving the citizen's income.
Keywords: J65; J68; 330; Grundeinkommen; Deutschland